Succession in Chinese family enterprises: the influence of cognitive, regulatory and normative factors - Man, Thomas Wing Yan; Mustafa, Michael; Fang, Yao (Inderscience, 2016)
Through an institution-based perspective, we investigate succession issues of Chinese family enterprises with a focus of how China's One Child Policy impacts the process. Based on an in-depth case study of two Chinese family firms, we find that the succession process is embedded in an institutional environment constituted by a multitude of intertwining moral, socio-economic, and politico-legal factors. To be more effective in this process, we recommend an earlier cultivation of the successors' positive values and attitudes towards the family enterprises, proper alignment between their knowledge and experience, provision of mentoring to them, and strengthening their effort in reflecting upon experience.